Effects of experimental parameters on simultaneous removal of SO2 and NO by VUV/H2O2 advanced oxidation process in a pilot‐scale photochemical spraying tower. Issue 3 (28th November 2018) - Xie, Wenxia; Xu, Chengwei; Zhang, Jun; Liu, Yangxian; Xi, Jianfei; Gu, Zhongzhu; Lv, Jianhong
Abstract: Background: Emissions of SO2 and NO from flue gas have caused serious environmental pollution issues. UV/vacuum ultraviolet(VUV)‐activated H2 O2 advanced oxidation technology is one of the most promising processes to realize the simultaneous removal of SO2 and NO. From the application perspective, it is necessary to carry out further research in a pilot‐scale photochemical reactor with industrial conditions and actual coal‐fired flue gas running conditions. Results: Results showed that SO2 removal efficiency can reach 100% under most experimental conditions. An increase of the VUV irradiation intensity, H2 O2 concentration and solution pH can promote NO removal, but the growth rate of that gradually slows down. It is not conducive to NO removal when the flue gas flow and NO concentration increases. Increasing liquid–gas ratio has dual effects on NO removal; NO removal efficiency increases at first, and then decreases sharply. SO2 concentration has no great impact on removal of NO. Results of ion chromatography (IC) demonstrate that SO4 2− and NO3 − are the major removal products of SO2 and NO. Conclusion: The VUV‐activated H2 O2 advanced oxidation technology is suitable for industrial application. The investment and operating costs of this technology are lower than those of the combined processes NH3 ‐SCR and Ca‐WFGD. © 2018 Society of Chemical Industry